Killer Kabbage [videorecording (DVD)] - Reed, Jude; Dotson, Michael; Witucki, Seth; Sciacca, Keith; Maurer, Ryan (X4 Pictures, 2024)
Cage and Gibson are two warriors making their living while traveling through a ravaged nomadic enviornment in the year 2224. They are recruited by a secret government agency to be sent back in time to stop a negligant science laboratory from unknowingly starting the cabbage apocalypse.